2018
DOI: 10.1021/acsomega.7b02055
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Electrochemical Transducer Platform for Neurotransmitters

Abstract: We have designed a flexible electrochemical transducer film based on PEDOT–titania–poly(dimethylsiloxane) (PTS) for the simultaneous detection of neurotransmitters. PTS films were characterized using various techniques such as transmission electron microscopy, scanning electron microscopy, atomic force microscopy, four probe electrical conductivity, ac-impedance, and thermomechanical stability. The electrocatalytic behavior of the flexible PTS film toward the oxidation of neurotransmitters was investigated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…The percolation region was found to be at PAg3 where the conductivity increased drastically beyond which the percolation was achieved. 40 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The percolation region was found to be at PAg3 where the conductivity increased drastically beyond which the percolation was achieved. 40 …”
Section: Resultsmentioning
confidence: 99%
“…The inset displays the equivalent circuit (Randles model) used to fit the Nyquist diagrams, which consists of a solution resistance R s connected in series with the double layer capacitance ( C dl ), charge transfer resistance ( R ct ), and Warburg impedance ( Z w ), respectively. 40 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, flexible sensors could capture target analytes more efficiently and showed higher quality signals. Several flexible electrochemical sensor platforms have reported for either in vitro or in vivo monitoring of different biomarkers and neurotransmitters [6][7][8][9][10][11][12][13]. Recently, some researches focused on the fabrication of flexible SERS for their biological applications, which including in situ detection based on wrapped the flexible sensor on a solid substrate; besides, few studies have reported the uses of flexible sensors for the direct detection of analytes in the liquid phase [14].…”
Section: Introductionmentioning
confidence: 99%